Cross-cultural measurement validation: an analysis of dissent, workplace freedom of speech, and perceived immediacy - Croucher SM; Kelly S; Ashwell D; Condon S; Tootell B (Taylor and Francis Group on behalf of the Eastern Communication Association, 2024)
Croucher and Kelly (2019) laid out guidelines to develop measures that can be used across cultures. The present study provides support for their guidelines, indicating that pancultural measurements cannot be behavioral and should not include unnecessary contexts; however, they should be worded as simplistically as possible. This study utilizes measures of dissent, perceived immediacy, and workplace freedom of speech in Australia, Canada, New Zealand, and the United States. Only the perceived immediacy measure, which follows Croucher and Kelly’s (2019) guidelines, maintained internal consistency.
Keywords: Measurement; validity; culture; pancultural